Impact of Development Perspective of HRM and Lesson Learned System of Knowledge Management on Project Success Through Project Management Competency Retention - Muhammad Mudassar Ghafoor; Kanwal Iqbal Khan; Yasin Muneer; Khawaja Hasnat Haider (JISR Management and Social Sciences & Economics, 2019)
This study was conducted to find out the impact of development perspective of Human Resource Management (HRM), and lesson learned system of knowledge management (KM) on project success with the mediation of project management competency retention (PMCR). The data was collected from 310 employees of the telecommunication industry. The results confirmed that the development perspective of HRM and lesson learned through the system of KM has a significant relationship with PMCR and project success. The intervening role of PMCR is also proved between lesson learned the system of KM and project success. The study presents new evidence to organizations for enhancing competency retention of employees and achieve project success.